5n-3(n-8)=4+3n

Simple and best practice solution for 5n-3(n-8)=4+3n equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5n-3(n-8)=4+3n equation:


Simplifying
5n + -3(n + -8) = 4 + 3n

Reorder the terms:
5n + -3(-8 + n) = 4 + 3n
5n + (-8 * -3 + n * -3) = 4 + 3n
5n + (24 + -3n) = 4 + 3n

Reorder the terms:
24 + 5n + -3n = 4 + 3n

Combine like terms: 5n + -3n = 2n
24 + 2n = 4 + 3n

Solving
24 + 2n = 4 + 3n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-3n' to each side of the equation.
24 + 2n + -3n = 4 + 3n + -3n

Combine like terms: 2n + -3n = -1n
24 + -1n = 4 + 3n + -3n

Combine like terms: 3n + -3n = 0
24 + -1n = 4 + 0
24 + -1n = 4

Add '-24' to each side of the equation.
24 + -24 + -1n = 4 + -24

Combine like terms: 24 + -24 = 0
0 + -1n = 4 + -24
-1n = 4 + -24

Combine like terms: 4 + -24 = -20
-1n = -20

Divide each side by '-1'.
n = 20

Simplifying
n = 20

See similar equations:

| 4=w/12 | | y-5+5= | | 11-4a=-7(a-1)+1 | | -(2x+3)=-5+7x | | 3x-3-x-4x=5x+12-12x | | b^2-4b+1=-5 | | 9(y-1)=4y+4 | | -6(r+6)=-37-5r | | -6b-6b=8-4b-7b | | p+7=8 | | (-x)-2x=(-7) | | 2=2-7n-2n | | 3x+4-2x-x=4x-4 | | -2(5x+5)+2x-1=-43 | | -2+3x=-6+7(6x-5) | | 5/k=2/7 | | 20-22+3= | | 2n+40=2n+10 | | 10=x*(x+3x) | | 8/3=5/b | | 4(8n-3)=-12+7n | | n/7=4/3 | | X^2(2x+3y-6)= | | 0=-16t^2+16t+672 | | cos(2x)*sin(4x)=0 | | -2x-4.5+7=1.8 | | 3/x=18 | | r/3=4/2 | | 12-7x=24x+23 | | 2/x=3 | | -3u=30 | | 3/x=5/3 |

Equations solver categories